Enhancing Protection and Monitoring in Modern Distribution Systems Using Smart Meter: A Review - Charansingh U. Ingle; Prakash G. Burade (International Journal of Electrical Power and Machine Systems, 2025)
Emerging distribution systems are witnessing a significant increase in the deployment of smart meters (SMs). Though, some remain hesitant about adopting SMs due to concerns related to health risks from radio wave exposure, fire hazards, and the privacy of user data. Additional key issues are high cost for energy suppliers, with perceived less advantages, as highlighted in detailed cost-benefit analyses. In some instances, existing SM applications have failed to justify their value. Numerous reports suggest that global SM rollouts have faced various challenges, leading to slow progress and rising skepticism. This has created a need for expanding the use of smart meters, particularly in areas like monitoring and protection within evolving electrical networks. Protection and monitoring are critical concerns for distribution providers, and they are eager to explore smart solutions to manage these functions effectively. This paper proposes several potential uses of smart meters to enhance the safety and reliability of distribution systems, with the expectation that these innovations will help validate and encourage future smart metering projects.
Keywords: Smart meters Distribution systems Protection and monitoring Power system reliability Smart grid applications